PENINGKATAN KEMAMPUAN MENULIS PUISI MELALUI MEDIA AUDIOVISUAL (VIDEO) PADA SISWA KELAS XI IPS SMA DARUSSALAM BLOKAGUNG BANYUWANGI TAHUN AJARAN 2022-2023 - Putri Nafisatul Masruroh; Rofiq, Asngadi (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2024)
This research aims to explain whether the use of audiovisual media (video) can improve the ability to write literary poetry in class XI IPS students at SMA Darussalam Blokagung Banyuwangi for the 2022-2023 academic year. This research is a quantitative research that shows variable This research uses quantitative descriptive analysis techniques by testing data validity and data reliability using the alpha formula. Data collection techniques were obtained by observing teachers and students, interviews, distributing questionnaires and documentation. The data analysis technique used in this research is simple linear regression. And the results of the questionnaire obtained from the researcher, carrying out validity, reliability and normality tests at a significance level of 0.05 in the r table for the number of respondents 34, were able to show that the Cronbach alpha value of variable X was 0.789. Meanwhile, variable Y is 0.780. each of these variables has high criteria.